2018
DOI: 10.1007/s00595-018-1652-9
|View full text |Cite
|
Sign up to set email alerts
|

Sternal semi-closure using a bioresorbable osteosynthesis device: a new method for delayed sternal closure

Abstract: The sternal semi-closure method decreases pulmonary and cardiac instability during DSC, making early DSC possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…26 Staged closure using a binder clip was described by Fuchigami et al 27 Tanaka et al revealed a semisternal closure with bioresorbable osteosynthesis device. 28 This is not available at our center. We used the blood collection bag, which can be used as a polyurethane sheet for covering the open sternum in the management of DSC.…”
Section: Discussionmentioning
confidence: 99%
“…26 Staged closure using a binder clip was described by Fuchigami et al 27 Tanaka et al revealed a semisternal closure with bioresorbable osteosynthesis device. 28 This is not available at our center. We used the blood collection bag, which can be used as a polyurethane sheet for covering the open sternum in the management of DSC.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al [12] reported that postoperative respiratory and hemodynamic condition were more stable with SFMX in fixing median sternotomy after congenital cardiac surgery. Sakashita et al [15] confirmed fixation sternotomy with SFMX promoted bone stability and decreased post-surgical pain.…”
Section: Discussionmentioning
confidence: 99%
“…SFMX has already been used for fixing rib fracture [9,10] or repair of flail chest [11]. Even more, Tanaka et al [12] reported that postoperative respiratory and hemodynamic condition were more stable with SFMX in fixing median sternotomy after congenital cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Different methods for sternal fixation, including different suture patterns, different steel wire quantities and novel titanium devices, have been tested to reduce mortality, morbidity, hospital stay, overall costs and psychological distress. [4][5][6][7][8] However, metallic implants may increase the inconvenience for some patients in the scenario of magnetic resonance imaging scans, security checks and personal privacy. Polyetheretherketone (PEEK) is a polyaromatic thermoplastic polymer with satisfactory biocompatibility and mechanical properties that has already been widely used in various surgical fields, including spine surgery, orthopaedic surgery and maxillo-facial surgery.…”
Section: Introductionmentioning
confidence: 99%